Shoreline Change Analysis on Enggano Island Using the Digital Shoreline Analysis System (DSAS): A Case Study of Kahyapu, Kaana, and Malakoni Villages - Arsyi Dafa Maulidan; Besperi; Agustin Gunawan; Khairul Amri; Gusta Gunawan (Departemen Teknik Kelautan Universitas Hasanuddin, 2026)
Coastal shoreline change is a dynamic process that significantly affects coastal ecosystems and human activities. This study quantitatively analyzed shoreline changes along the coast of Enggano Island, Bengkulu Province, during the period 1993–2025, focusing on Kahyapu, Kaana, and Malakoni Villages. Shoreline extraction was performed using Landsat imagery from 1993, 2009, and 2025 after radiometric and geometric corrections, employing the Modified Normalized Difference Water Index (MNDWI) and tidal correction based on MIKE 21 modeling and bathymetric data. Shoreline change rates were calculated using the Digital Shoreline Analysis System (DSAS) with 2,052 transects at 10 m spacing and the parameters Net Shoreline Movement (NSM), End Point Rate (EPR), and Linear Regression Rate (LRR). The results indicate that shoreline retreat due to erosion dominates all study areas. During 1993–2009, average erosion rates ranged from −0.42 to −0.63 m/year and increased markedly during 2009–2025, reaching up to −1.26 m/year in Malakoni Village. Long-term trend analysis for 1993–2025 shows the highest erosion rate in Malakoni (−0.87 m/year), followed by Kaana (−0.56 m/year) and Kahyapu (−0.44 m/year). Accretion occurred only locally and at relatively low rates, insufficient to offset land loss. These findings confirm that the coastal areas of Enggano Island are highly vulnerable to continuous erosion and emphasize the need for integrated and sustainable coastal management strategies.